2009
DOI: 10.1177/1046496409334359
|View full text |Cite
|
Sign up to set email alerts
|

Can High Group Cohesion Be Harmful?

Abstract: High group cohesion is considered to be beneficial and lead to better performance. This qualitative case study describes a case in which high social cohesion led to a deterioration in a team's performance. The aim of the present study was to investigate the relationships between performance in a team sport and social psychological group phenomena such as cohesion, conformity, groupthink, and group polarization. The participants were members of a junior-league ice-hockey team, consisting of three adult coaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Consequently, poor group decisions can be made, such as International Review of Sport and Exercise Psychology 239 altering team strategies that ultimately end up decreasing team success (Wittenbaum et al, 2004). Teams need to be wary of these potential repercussions -particularly highly cohesive teams who are especially prone to groupthink (e.g., Rovio, Eskola, Kozub, Duda, & Lintunen, 2009) -and be resolute on finding solutions that will most benefit the team, even if this causes disagreements throughout the process (Janis, 1972;Wittenbaum et al, 2004).…”
Section: Regulation Of Team Performancementioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, poor group decisions can be made, such as International Review of Sport and Exercise Psychology 239 altering team strategies that ultimately end up decreasing team success (Wittenbaum et al, 2004). Teams need to be wary of these potential repercussions -particularly highly cohesive teams who are especially prone to groupthink (e.g., Rovio, Eskola, Kozub, Duda, & Lintunen, 2009) -and be resolute on finding solutions that will most benefit the team, even if this causes disagreements throughout the process (Janis, 1972;Wittenbaum et al, 2004).…”
Section: Regulation Of Team Performancementioning
confidence: 97%
“…However, merely targeting team cohesion in team building fails to account for a likely substantial amount of variance from the aforementioned teamwork variables that are involved in improving team effectiveness. Furthermore, highly cohesive teams are not inevitably effective teams; in some cases, high cohesion has even been associated with decreased team performance (e.g., Hardy, Eys, & Carron, 2005;Rovio et al, 2009). Finally, Martin et al (2009) found that International Review of Sport and Exercise Psychology 243 while cohesion has been the most frequently targeted outcome variable in team building in sport, this was among the variables least influenced by team-building interventions.…”
Section: Measuring Teamworkmentioning
confidence: 98%
“…It also suggests a moderating variable that may strengthen the link between cohesion and attitudes to performance, particularly in tasks requiring innovation. In particular, while cohesion has been found to potentially increase pressure to conform (Rovio, Eskola, Kozub, Duda, & Lintunen, ), professional salience may act to minimize this risk of conformity by drawing attention to job‐related differences.…”
Section: Discussionmentioning
confidence: 99%
“…Group cohesiveness in any type of team seems to increase over time, particularly when there is a leader in the group [16]. Other elements that affect group cohesiveness include team size, degree of democratic behavior within a group, participation, and satisfaction [17].…”
Section: Team Cohesion Literaturementioning
confidence: 99%
“…For example, [17] shows that high social cohesion within a group can sometimes lead to poor performance. One explanation for this negative relationship is that a team with high social cohesion may actually lead to high levels of group conformity and a reluctance to criticize a teammate's performance.…”
Section: Team Cohesion Literaturementioning
confidence: 99%